A work and systems and procedures study on Malin Garments - Cerrero, Geraldine (College of Engineering, 1998)
Malin Garments is a company producing high quality products to be exclusively exported abroad. They transact their business with trading offices that provides them with contract orders. The company manufactures children's clothing. They cater for children whose age's ranges from 6 months to 24 months. The number of units to be produced depends upon each particular contract. The activities in their production, starting from the confirmation of the deal until the shipment of the finished products, lasts for approximately three months. The study was done towards the end of their current contract. This study aimed to increase productivity and efficiency of Malin Garments through improved working conditions, minimization of delays, reduction in movement of man and materials, establishment of standard time, and standardization of work policies and procedures. Through careful observation and analysis of the present system of the company, the group was able to identify low productivity and delays as their major concerns. In the course of the study, it was recognized that the company does not have standard policies and procedures, leading to disorderly behaviors of workers and inefficient work methods. It was also observed that their working area lacked proper maintenance resulting to poor conditions in the plant. Furthermore it was noted that work in process materials suffer too much handling due to limitations in the given layout and lack of a transport system. In addition, the administration does not have an effective system for monitoring that sometimes contain defects or damages, delaying their production process further. Although all of the problem areas observed by the group contribute to their low productivity and delays, the core was determined to be their obvious handicap in their systems and procedures. Once this concern is prioritized, the company will find it easier to effect all the other needed improvements. The group generated alternatives in attempt to find solutions to these problems. Thorough evaluation of these alternatives led to the recommendations believed to best induce the desired results. After the identification and documentation of standard policies and procedures, the company should shift its attention to (1) maintenance of working environment, (2) improving the present layout, and (3) introduction of transport containers. The implementation of these proposed solutions assures a major overall improvement to the system of Malin Garments.